Prediksi Jumlah Mahasiswa Baru Tahun 2023 Menggunakan Metode Regresi Linier Pada Universitas Swadaya Gunung Jati Cirebon - Dani Dani (KOMPUTEK, 2023)
Abstract Acceptance of new students is a important activity in tertiary institutions to obtain the number of new students. The number of new students every year is uncertain, sometimes increasing and sometimes decreasing. It is proven by the acceptance of new students in 2020 the number of new students is 2800 students, then in 2021 there has been an increase of 2678 students and in 2022 there has been a decrease in the number of new students by 2631 students. The uncertain number of new students makes all policies and decisions in planning different each year, it is necessary to predict the number of new students in 2023 so that policies and decisions can be determined earlier. One method for predicting the number of new students in 2023 can use the linear regression method. This method has several stages, namely the quantitative approach method and the descriptive approach method, and there is data analysis and then classifies the data according to research needs so that it can determine a model in predicting new student admissions. The dataset used is PMB data from 2019 to 2022 from 7 faculties and postgraduate schools, namely the number of registered student data, the number of graduated student data and the number of registered student data then the total data per study program at the Gunung Jati Swadaya University. The results of the prediction of the number of new students in 2023 at the Gunung Jati Swadaya University, Cirebon using The linear regression method yields the predicted value of each study program as many as 650, 48, 747, 256, 23,77,32, 52,48,240,33,87,12,31,167,26,237, after adding up the total predicted value is 2705 the number of students in 2023 with the number of students in 2022 is 2631 students self, the predicted results will increase by 74 students or 3% of the number of new students in 2022. Keywords: Linear Regression. Prediction of the Number of New Students, Gunung Jati Self-Help University Abstrak Penerimaan mahasiswa baru merupakan aktivitas penting pada perguruan tinggi untuk memperoleh jumlah mahasiswa baru. Jumlah mahasiswa baru tiap tahunnya tidak menentu, kadang mengalami peningkatan dan bisa juga mengalami penurunan.Terbukti dengan penerimaan mahasiswa baru tahun 2020 jumlah mahasiswa baru sebanyak 2800 mahasiswa, kemudian pada tahun 2021 mengalami kenaikan sebanyak 2678 mahasiswa dan pada tahun 2022 menglami penurunanjumlah mahasiswa baru sebanyak 2631 mahasiswa.Tidak menentunya jumlah mahasiswa baru membuat semua kebijakan dan keputusan dalam menyusun perencanaan berbeda beda tiap tahunnya, maka perlu adanya prediksi jumlah mahasiswa baru tahun 2023 agar dapat menentukan kebijakan dan keputusan lebih awal. Salah satu metude untuk memprediksi jumlah mahasiswa baru tahun 2023 dapat menggunakan metoderegresi linier. Metode ini memiliki beberapa tahapan yaitu dengan metode pendekatan kuantitatif dan metode pendekatan deskriptif,dan ada analisis data kemuadian mengkalsifikasikan data sesuai dengan kebutuhan penelitian agar dapat menetukan suatu model dalam prediksi penerimaan mahasiswa baru dataset yang digunakan merupakakan data pmb dari tahun 2019 samapai dengan tauhn 2022 dari 7 fakultas dan sekolah pascasrjana yaitu jumlah data mahasiswa yang mendaftar, jumlah data mahasiswa yang lulus dan jumlah data mahasiswa yang registrasi kemudian jumlah data total perprodi pada universitas swadaya gunung jati.Hasil dari prediksi jumlah mahasiswa baru tahun 2023 pada universitas swadaya gunung jati cirebon dengan menggunakn metode regresi linnier di dapat nilai prediksi dari masing masing prodi sebanayk 650, 48, 747, 256, 23,77,32, 52,48,240,33,87,12,31,167,26,237, setelah di jumlahkan di dapat nilai total hasil prediksi 2705 jumlah mhasiswa tahun 2023 dengan jumlah mahasiswa tahun 2022 sebanyak 2631 mahasiswa maka hasil prediksi mengalami kenaikan sebanyak 74 mahasiswa atau sebesar 3% dari jumlah mahasiswa baru pada tahun 2022. Kata Kunci: Regresi Linier; Prediksi Jumlah Mahasiswa Baru; Universitas Swadaya Gunung Jati.